2022
DOI: 10.1002/lio2.742
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of lymph node metastasis in head and neck squamous cell carcinoma using deep learning

Abstract: Background: To build an automatic pathological diagnosis model to assess the lymph node metastasis status of head and neck squamous cell carcinoma (HNSCC) based on deep learning algorithms. Study Design: A retrospective study. Methods: A diagnostic model integrating two-step deep learning networks was trained to analyze the metastasis status in 85 images of HNSCC lymph nodes. The diagnostic model was tested in a test set of 21 images with metastasis and 29 images without metastasis. All images were scanned fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Regarding the performance of AI tools in histology, all studies reported an accuracy over 90%, except for 2 papers. 24 , 27 They also reported excellent performance via AUC calculations, as well as high sensitivity and specificity. Different types of AI algorithms were tested in the included studies, from supervised machine learning systems (e.g., SVM) to deep learning systems such as CNNs.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Regarding the performance of AI tools in histology, all studies reported an accuracy over 90%, except for 2 papers. 24 , 27 They also reported excellent performance via AUC calculations, as well as high sensitivity and specificity. Different types of AI algorithms were tested in the included studies, from supervised machine learning systems (e.g., SVM) to deep learning systems such as CNNs.…”
Section: Discussionmentioning
confidence: 92%
“…In general, performance of the development dataset were 100% for accuracy, sensitivity, and specificity; whereas in the test dataset sensitivity was 100%, specificity 75.9%, and accuracy 86%. 27 Only 1 study regarded salivary glands tumors. Lopez-Janeiro et al used a tree model algorithm to diagnose different histotypes of malignant tumors on 115 samples of salivary glands.…”
Section: Resultsmentioning
confidence: 99%
“…Only 12 studies (19%) out of 63 studies investigating LN metastasis provided a detailed analysis of false-positive predictions in metastatic LN detection. Based on the gathered data, LN sinus histiocytes were the most common false positively identified region mentioned by six studies 29 , 31 , 56 , 68 , 90 , 94 followed by secondary lymphoid follicles (germinal centers), 56 , 64 , 94 connective tissue, 31 , 64 out-of-focus areas, 68 and slide artifacts. 50 The most common metastatic regions misclassified as negative were micrometastatic lesions 61 , 64 as well as histiocyte-like tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…When designing an automated diagnostic tool, it is important to minimize the chance of false-negative decision, where a metastatic LN is assigned to a “healthy” metastasis-free class, which is reflected by sensitivity metric. Two studies in our analysis proposed ResNet-based solutions that achieved a perfect 1.00 sensitivity in gastric cancer 55 and head and neck cancer 56 datasets consisting of 40 gastric cancer patients and 50 head and neck cancer images, respectively. The proposed metastasis detection systems reached lower yet still competitive false-positivity (specificity) scores of 0.9994 in gastric cancer and 0.759 in head and neck cancer studies, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation